The prevalence of ocular defects and the provision of eye care in adults with learning disabilities living in the community - Woodhouse, J.Margaret; Griffiths, Christine; Gedling, Alison (Ophthalmic & physiological optics, 2000)
Most people with learning disabilities now live in the community rather than in institutions, and community services need to be targeted appropriately. Vision screening was carried out in community Day Care Centres for adults with learning disabilities. One hundred and fifty four subjects took part, and screening was successful in 148 subjects, using retinoscopy and standard acuity tests, including preferential looking. The previously reported high prevalence of refractive errors, strabismus and pathological defects amongst people with learning disabilities was confirmed. Over 60% of subjects had below-normal distance acuity, which in many cases was exacerbated by uncorrected refractive errors. In all, 41% of subjects could have benefited from distance spectacles, and 56% from spectacles for near tasks. The lack of adequate spectacles was particularly high amongst adults with more severe learning disabilities. The study highlights the current lack of adequate eye care for people with learning disabilities, and demonstrates that eye examinations are possible for the majority of individuals. There is a need for greater awareness amongst families/carers and amongst optometrists to address this important issue.